2009
DOI: 10.1021/es901041p
|View full text |Cite
|
Sign up to set email alerts
|

An Index for Assessing Demographic Inequalities in Cumulative Environmental Hazards with Application to Los Angeles, California

Abstract: Researchers in environmental justice contend that lowincome communities and communities of color face greater impacts from environmental hazards. This is also of concern for policy makers. In this context, our paper has two principal objectives. First, we propose a method for creating an index capable of summarizing racial-ethnic and socioeconomic inequalities from the impact of cumulative environmental hazards. Second, we apply the index to Los Angeles County to illustrate the potential applications and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 27 publications
8
127
1
Order By: Relevance
“…The multipollutant profile approach developed will be applied to estimates of air pollution concentrations for NO 2 , PM 2.5 , diesel (road), and diesel (offroad) exposures obtained using a recently published paper. 18 Briefly, NO 2 estimates were obtained via a land-use regression. The variables used for NO 2 model selection included land-use information (e.g., commercial and industrial), road network, traffic, population distribution, physical properties, and remote sensing-derived greenness and soil brightness.…”
Section: Methodsmentioning
confidence: 99%
“…The multipollutant profile approach developed will be applied to estimates of air pollution concentrations for NO 2 , PM 2.5 , diesel (road), and diesel (offroad) exposures obtained using a recently published paper. 18 Briefly, NO 2 estimates were obtained via a land-use regression. The variables used for NO 2 model selection included land-use information (e.g., commercial and industrial), road network, traffic, population distribution, physical properties, and remote sensing-derived greenness and soil brightness.…”
Section: Methodsmentioning
confidence: 99%
“…Dong et al [27] mentioned that SO 2 emission is unequally exposed in the different regions in China due to the uneven evolution of industrial activities. The NO X emission pattern is a well-known pollutant proxy used in studies because it is mostly caused by traffic and urbanization, although people in different social classes or groups are exposed to it unequally [11,12,25,[28][29][30]. Gu et al [31] found the regional disparity in NO X emission trend in China was that less-developed provinces suffer more growth rate of NO X emission than rich provinces due to the lack of strict environmental regulation to control emission in the less-developed provinces.…”
Section: Air Pollution In Chinamentioning
confidence: 99%
“…Despite the decrease of SO2 and NOX emissions during the period of the 12th FYP, there is a significant regional disparity in both emissions which needs more attention to improve the local air quality [28]. …”
Section: Air Pollution In Chinamentioning
confidence: 99%
“…For instance, an index can be created for racial/ethnic and socio-economic inequalities (Su et al 2009), or for social determinants (Salinas et al 2012). Matrices (WHO 2010) and algorithms (NEJAC 2010;Zartarian et al 2011;Hastings et al 2013) have been developed to help identify highest comparative risks.…”
Section: Modulating Factorsmentioning
confidence: 99%